mTORC1-selective inhibitors rescue cellular phenotypes in TSC iPSC-derived neurons - Buttermore, Elizabeth D.; Srinivasan, Gayathri Rajaram; Jumo, Hellen; Swanson, Amanda C.; O’Kelly, Benjamin; Makhortova, Nina R.; Sahin, Mustafa; Tzannis, Stelios T. (Frontiers in Neuroscience, 2025)
The mechanistic target of rapamycin (mTOR) pathway plays an important role in regulating multiple cellular processes, including cell growth, autophagy, proliferation, protein synthesis, and lipid synthesis, among others. Given the central role of this pathway in multiple cellular processes, it is not surprising that mTOR pathway dysregulation is a key mechanism underlying several neurological disorders, including Tuberous Sclerosis Complex (TSC). TSC patients typically present with pathogenic variants in the TSC1 or TSC2 genes, which encode proteins forming a complex that plays an important role in modulating mTOR activity. We previously reported cellular and functional deficits in induced pluripotent stem cell (iPSC)-derived neurons from TSC patients. These deficits were reversed by inhibiting mTOR activity using rapamycin treatment, revealing the role of mTOR signaling in the regulation of cell morphology and hyperexcitability phenotypes in TSC patient-derived neurons. However, chronic rapamycin treatment inhibits both mTORC1 and mTORC2 activity and its clinical use is associated with significant side effects. With the development of novel mTORC1-selective compounds, we aimed to assess whether selective inhibition of mTORC1 likewise reversed the cellular and functional deficits found in TSC patient-derived neurons. Our results indicate that the novel, selective mTORC1 inhibitors nearly fully reversed the cellular and functional deficits of TSC2–/– iPSC-derived neurons in a fashion and magnitude similar to rapamycin, as they all reversed and near-normalized their neuronal hyperexcitability and abnormal morphology as compared to the DMSO-treated cells. These data suggest that mTORC1-specific compounds could provide clinical therapeutic benefit similar to rapamycin without the same side effects.